Interpretation of intraoperative recurrent laryngeal nerve monitoring signals: The importance of a correct standardization. (April 2016) - Calò, Pietro Giorgio; Medas, Fabio; Gordini, Luca; Podda, Francesco; Erdas, Enrico; Pisano, Giuseppe; Nicolosi, Angelo
Abstract: Introduction: Despite the increasingly broad use of intraoperative neuromonitoring, review of the literature and clinical experience confirms there is little uniformity in application of and results across different centers. The aim of this study was to evaluate the ability of intraoperative neuromonitoring with a standardized evaluation of the signals to predict the postoperative functional outcome and its role in reducing the postoperative recurrent nerve palsy rates. Methods: 2365 consecutive patients underwent thyroidectomy by a single surgical team: in 1356 patients (group A) with intraoperative neuromonitoring, in 1009 (Group B) without it. Results: In group A a loss of signal was observed in 37 cases: we had 29 true positive cases, 1317 true negative, 8 false positive, and 2 false negative. Accuracy was 99.26%, positive predictive value 78.38%, negative predictive value 99.85%, sensitivity 93.55%, and specificity 99.4%. 29 unilateral nerve paralysis were observed (2.13%), 23 (1.69%) transient and 6 (0.44%) permanent. In group B 26 unilateral paralysis were observed (2.57%), 20 (1.98%) transient and 6 permanent (0.59%) Differences were not statistically significant. Conclusions: Intraoperative neuromonitoring is highly predictive of the postoperative nerve function. We obtained a very high sensitivity and negative predictive value, but also a good specificity and positive predictive value. For these reasons, in selected patients with loss of signal, the surgical strategy can be reconsidered. On the other hand, this study failed to demonstrate a statistically significant decrease in the nerve paralysis rate. Further studies are needed to better evaluate the real benefit of this technique. Highlights: Intraoperative neuromonitoring is highly predictive of the postoperative nerve function. Standardization permits high sensibility and negative predictive value, but also specificity and positive predictive value. In selected patients with loss of signal the surgical strategy can be reconsidered. This study failed to demonstrate a statistically significant decrease in the nerve paralysis rate. Further studies are needed to better evaluate the real benefit of this technique.